Exploring the Impact of Digital Platforms on SME Internationalization: New Zealand SMEs Use of the Alibaba Platform for Chinese Market Entry. Issue 2 (3rd April 2018) - Jin, Huijun; Hurd, Fiona
ABSTRACT: Digital platforms have changed the way in which Asia-Pacific firms operate across borders, however, the impact of digital platforms on entry strategy is under-researched in current International Business literature. This study aims to explore how digital platforms impact New Zealand small and medium-sized (SMEs) companies' entry into the Chinese market. The results of case study interviews conducted with four SMEs suggest that digital platforms ease entry barriers to some extent, particularly in helping overcome resource constraints and facilitating access to networks. However, the participating firms still required local staff as a key part of successful market entry.